A CROSS-SECTIONAL STUDY ON IMPLEMENTATION OF e-SANJEEVANI SERVICES IN RURAL AREAS OF KALABURAGI DISTRICT - TANIYA JACOB; PRASHANT KUMAR; MOHAMMAD WASEEM FARAZ ANSARI; POONAM P SHINGADE; I AMRUTA SWATI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: India adopted national telemedicine service – “e-Sanjeevani” on November 2019, based on “Hub and Spoke Model” where Health and Wellness Centers under Ayushman Bharat (AB-HWCs) will be the spokes and MBBS/specialty doctors will be the hub. It aims to overcome the shortage of doctors/specialists at the ground level, reduce the burden at higher centers, and inculcate expert medical advice seeking behavior among rural people. The objectives of the study are to assess the implementation of e-Sanjeevani services in rural Kalaburagi and to identify the challenges faced by the service providers of e-Sanjeevani in rural Kalaburagi. Methods: A cross-sectional study was conducted across the AB-HWCs in the rural areas of Kalaburagi district over a period of 3 months. Multistage sampling was done, maintaining a constant of 50%. The total sample size was 75 HWCs. The implementation of e-Sanjeevani was assessed using a pre-designed, pre-tested, and semi-structured questionnaire. The data collected were entered into MS Excel and frequency, percentage, t-test, and Chi-square test were employed for analysis. Results: e-Sanjeevani is implemented in all the selected subcenters (100%) whereas it was implemented only in 14 (58.35%) of the selected PHCs in Kalaburagi district. The service providers face multiple challenges such as unavailability of specialists online (52.3%), long waiting time (43.1%), network issues (41.5%), and unavailability of investigations/drugs prescribed by specialists (40%). Mean grading of e-Sanjeevani on a scale of 1-10 by service providers in subcenters (7.25±1.76) was also statistically significant than in PHCs (6.07±1.82). Conclusion: Although e-Sanjeevani is implemented in all subcenters in Kalaburagi district, its smooth functioning is hampered by various factors which call for strengthening of specialist availability and other facilities.